A stochastic, daily time-step model for the conjunctive use of surface water, groundwater, desalination and water reclamation for municipalities - Braune, Erika Gertrud (Stellenbosch : Stellenbosch University, 2020)
Thesis (MEng)--Stellenbosch University, 2020.